To collapse or not to collapse blastocysts before vitrification? A matched case-control study on single vitrified-warmed blastocyst transfers. Issue 4 (October 2022) - Kovačič, Borut; Taborin, Marjan; Vlaisavljević, Veljko; Reljič, Milan; Knez, Jure
Highlights: Blastocyst collapsing is an invasive intervention and still not evidence based This is the first matched case-control study analysing live births and neonatal outcome Collapsing resulted in better survival and a non-significant 5% increase in live births To confirm a 5% improvement, more than 2500 cases will be needed No difference was found in neonatal outcomes Abstract: Research question: Does laser-induced artificial blastocoel collapse result in better blastocyst cryopreservation survival and a higher live birth rate (LBR) in comparison with intact counterparts? Design: Half of the supernumerary blastocysts from IVF cycles were randomly selected before vitrification for laser-induced artificial collapsing or vitrification in intact form. A matched case-control study of first transfers of single blastocysts artificially collapsed (case) or intact (control) before vitrification was conducted. Controls were matched to cases on a 1:1 ratio by female age, parity, fresh and vitrified cycle protocol, blastocyst age and quality, resulting in 309 case-control pairs. Results: The two groups were comparable in terms of their characteristics. Survival rates in the case and control groups (97.8% and 95.7%; P  = 0.133) were comparable, but the optimal survival rate was higher in the case group (78.2% and 69.3%; P  = 0.03). Clinical pregnancy rates (38.2% and 35.3%; P  = 0.518), miscarriage rates (15.2% and 22%; P  = 0.190), LBR per transfer (32.4% and 27.5%; P  = 0.221) and LBR per warmed blastocyst (31.6% and 26.3%; P  = 0.137) were not statistically different between the case and control groups. No significant difference in preterm births (11.1% versus 15.7%), birthweights (3333 ± 723 g versus 3304 ± 609 g) or sex ratio (49.3% versus 50.7% boys) was observed between the two groups. No major malformations were detected in the study population. Conclusions: Compared with vitrification of intact blastocysts, collapsed blastocysts resulted in a significantly higher optimal survival rate, and although they resulted in a 5% higher LBR, this was not significant for the chosen sample size. Neonatal outcomes were comparable in the two groups. Graphical abstract: Image, graphical abstract